Science, Technology, Engineering and Mathematics Methodology applied to the Teaching and Learning Process of Natural Sciences (Docentes 2.0 Journal, 2021)
Globalization and the emergence of the technological era have generated changes in the most demanding trades and professions worldwide. Some have disappeared, and other new ones arise; in addition, society's problems require integral and not partial solutions, according to the areas of knowledge. The objective that guided this research was to analyze the incidence of STEM in the teaching-learning process in the natural sciences of students in the fifth year of elementary school. For this purpose, action research with a qualitative approach was developed in four phases: planning, action, observation, reflection. Learning in natural sciences under STEM methodology was limited to fifth-grade teachers and students of the public Santo Ángel Educational Institution in Bucaramanga, Colombia. For this purpose, was chosen a sample of 10 key informants, widely knowledgeable, directly related to the research, distributed in this way, one teacher director, four classroom teachers, and five students. As a result, when applying STEM as a natural science learning methodology, the students achieved good adaptability and acceptance to the work system and a significant improvement in their performance in the subject. In conclusion, the STEM approach showed overall effectiveness in the teaching-learning process of natural sciences through interdisciplinary activities.
Keywords: STEM; Natural Sciences; Teaching; Learning